Politics and International Environmental Law in Global Perspective - Atika Sari, Diah Apriani; Triatmodjo, Marsudi; Purwanto, Harry (Pandecta Research Law Journal, 2024)
Global environmental politics refers to the ways in which politics is practiced in various places to change or protect the environment. This means that global environmental issues and related political activities can occur at local, national, transnational, regional, or international levels, depending on the location, scale, or environmental issues being addressed. This research is normative, by a conceptual approach derived from several approaches of international legal and political theory. Environmental politics also transforms state practices in understanding state sovereignty and the international system. State sovereignty is often cited as a reason that limits the development of a country’s environmental policies. Globalization creates a debate between sovereignty and the influence of national interests in policy-making. Political authority is expressed as sovereignty, making it very challenging to reach agreements on global environmental issues when they conflict with national interests. Nevertheless, global politics offers opportunities for international cooperation in addressing global environmental problems.